Bosentan treatment of digital ulcers related to systemic sclerosis: results from the RAPIDS-2 randomised, double-blind, placebo-controlled trial. Issue 1 (30th August 2010) - Matucci-Cerinic, Marco; Denton, Christopher P; Furst, Daniel E; Mayes, Maureen D; Hsu, Vivien M; Carpentier, Patrick; Wigley, Fredrick M; Black, Carol M; Fessler, Barri J; Merkel, Peter A; Pope, Janet E; Sweiss, Nadera J; et al.
Abstract : Objectives: Ischaemic digital ulcers (DUs) are common in patients with systemic sclerosis (SSc) and are a cause of disease-related morbidity. In an earlier trial, treatment with bosentan, an oral endothelin receptor antagonist, reduced the occurrence of new DUs by 48%. The present study (RAPIDS-2, for 'RAndomized, double-blind, Placebo-controlled study with bosentan on healing and prevention of Ischemic Digital ulcers in patients with systemic Sclerosis') was conducted to more fully evaluate the effects of bosentan treatment on DUs associated with SSc. Methods: This double-blind, placebo-controlled trial conducted at 41 centres in Europe and North America randomised 188 patients with SSc with at least 1 active DU ('cardinal ulcer') to bosentan 62.5 mg twice daily for 4 weeks and 125 mg twice daily thereafter for 20 weeks (n=98) or matching placebo (n=90; total 24 weeks). The two primary end points were the number of new DUs and the time to healing of the cardinal ulcer. Secondary end points included pain, disability and safety. Results: Over 24 weeks, bosentan treatment was associated with a 30% reduction in the number of new DUs compared with placebo (mean±standard error: 1.9±0.2 vs 2.7±0.3 new ulcers; p=0.04). This effect was greater in patients who entered the trial with more DUs. There was no difference between treatments in healing rate of the cardinal ulcer or secondary end points of pain and disability. Peripheral oedema and elevated aminotransferases were associated with bosentan treatment. Conclusions: Bosentan treatment reduced the occurrence of new DUs in patients with SSc but had no effect on DU healing. Bosentan was well tolerated and may be a useful adjunct in the management of patients with SSc with recurrent DUs.